The impact of first and second eye cataract surgeries on falls: a prospective cohort study - Feng, Y.; Meuleners, L.; Fraser, M.; Brameld, K.; Meuleners, Lynn (Dove Medical Press Ltd., 2018)
Purpose: The purpose of this study was to investigate the impact of the first and second eye cataract surgeries on the risk of falls in participants with bilateral cataract and to determine which changes in visual measures are associated with changes in the number of falls throughout the cataract surgery process. Patients and methods: Fifty-five older adults with bilateral cataract aged 55+ years were assessed at three time points during the cataract surgery process, and they completed a falls diary. Two separate generalized estimating equation–negative binomial models were undertaken to assess changes in the number of falls before first eye cataract surgery, between first and second eye surgeries, and after second eye cataract surgery and which changes in visual measures were associated with changes in the number of falls. Results: After adjusting for potential confounding factors, the risk of falls decreased by 54% (incidence rate ratio (IRR) =0.458, 95% CI=0.215–0.974, p=0.04) after first eye cataract surgery only, compared with the period before first eye surgery. The risk of falls decreased by 73% (IRR =0.268, 95% CI =0.114–0.628, p=0.002) after second eye cataract surgery, compared with the period before first eye surgery. Improved binocular visual acuity (IRR =5.488, 95% CI =1.191–25.282, p=0.029) and contrast sensitivity (IRR =0.257, 95% CI =0.070–0.939, p=0.040) were associated with a decrease in the number of falls. Conclusion: The study found that first and second eye cataract surgeries reduced the risk of falls among a cohort of bilateral cataract patients with relatively good baseline vision. This suggests that timely first and second eye cataract surgeries could play an important role in reducing the burden due to falls among older adults with cataract.